Influence of microstructure on magnetic and dielectric performance of Bi2O3-doped MgCd ferrites for high frequency antennas. Issue 9 (15th June 2019) - Gan, Gongwen; Zhang, Dainan; Zhang, Qing; Wang, Gang; Huang, Xin; Yang, Yan; Rao, Yiheng; Li, Jie; Xu, Fang; Wang, Xueying; Chen, Ray T.; Zhang, Huaiwu
Abstract: The effects of microstructure on the magnetic and dielectric properties of Mg0.6 Cd0.4 Co0.05 Fe1.95 O4 spinel ferrites with the addition of 2.5 wt% Bi2 O3 are investigated mainly for high frequency applications. The measurement results reveal that composites processed via low temperature co-fired ceramic (LTCC) technology at different sintering temperatures (900 °C, 920 °C, 930 °C, and 940 °C) possess excellent equivalent permeability ( μ ′) and permittivity ( ε ′) (at 940 °C, μ ′≈ ε ′≈25), over a long frequency range from 1 to 100 MHz. The results also indicate that densification sintering results in ultra low dielectric loss tan δ ε and magnetic loss tan δ μ (tan δ ε ≈0.003, tan δ μ ≈0.035). In addition, the samples present enhanced magnetic properties, such as high saturation magnetization (approximately 37.94 emu/g) and appropriate coercivity (approximately 60.5 Oe) at 940 °C. This research presents the prospect of wide application of MgCd ferrites in high frequency applications.